Existence of Periodic Solutions for Nonlinear Fully Third-Order Differential Equations. (6th April 2020) - Zhang, Yunfei; Pei, Minghe
Abstract : In this paper, we study the existence of periodic solutions to nonlinear fully third-order differential equation x ‴ + f t, x, x ′, x ″ = 0, t ∈ ℝ ≔ − ∞, ∞, where f : ℝ 4 ⟶ ℝ is continuous and T -periodic in t . By using the topological transversality method together with the barrier strip technique, we obtain new existence results of periodic solutions to the above equation without growth restrictions on the nonlinearity. Meanwhile, as applications, an example is given to demonstrate our results.